Analysis of the Mechanical Properties and Mechanism of Zinc Ion-Contaminated Red Clay - Jiaming Li; Shibin Tang; Xuejun Chen (Advances in Materials Science and Engineering)
To study the effects of different concentrations of zinc ions on the mechanical strength, material composition, and microstructure of red clay, a triaxial test, an x-ray diffraction test, an x-ray fluorescence spectrometry test, a scanning electron microscopy test, and a mercury intrusion test were carried out on contaminated soil to investigate the mechanisms of zinc ion-contaminated red clay. The results show that the higher the concentration of zinc ions, the smaller the shear strength and cohesion of the red clay. The internal friction angle is increased first and then decreased. From material composition, zinc ion makes montmorillonite and hemite disappear in red clay. With the increase of zinc ion concentration, quartz semiquantitative increase and kaolinite semiquantitative decrease and the content of SiO2, Fe2O3, and Na2O reduces. Microscopically, the structure of red clay changes from floc structure to granular and aggregate structure after the zinc ions are added, while the contact of the particles is converted to point contact. With the increase of the concentration of zinc ions, the porosity and the fractal dimension of the red clay gradually increase, and the stability of the granular structure is weakened.